The Effective Communication using SBAR (Situation, Background, Assessment, Recommendation) of Patient Handover in Inpatient Installation - Irawati, Roossy; Widodo, Arif; Yulian, Vinami (Jurnal Berita Ilmu Keperawatan, 2025)
The quality of nursing services is the main indicator of the quality of health services and is one of the determining factors for the image of health service institutions in the eyes of the community. The quality of nursing services has a relationship with patient safety. The relationship can influence the behavior of the person in doing something including the implementation of nursing and patient safety in communicating effectively; one of them is when the nurse does the handover. This study aims to evaluate the ability of nurses to carry out effective communication using the SBAR (Situation, Background, Assessment, Recommendation) method in Inpatient Installations in special hospitals. For this research can be done based on EC no. IP.03.01/D.XXV.2.3/8487/2024. The research method used was observation and questionnaires covering SBAR items, with selected respondents based on the criteria: age, education, and working period. Sixty-one nurses were taken as a sample. The results of the analysis indicated that the nurses' communication skills in the category were very good, with the highest scores in the aspects of Situation (97%) and Background (96%), while Assessment (75%) and Recommendation (95%) indicated an opportunity for improvement. The study also found that effective communication is critical for patient safety, with potential for improvement through additional training and interdisciplinary collaboration. These findings assert the importance of applying the SBAR method to improve communication within the medical team, which in turn can contribute to the improvement of patient safety and satisfaction.